Impacts of climate and land cover variability and trends on springtime East Asian dust emission over 1982–2010: A modeling study. (1st June 2021) - Tai, Amos P.K.; Ma, Perry H.L.; Chan, Yuk-Chun; Chow, Ming-Keung; Ridley, David A.; Kok, Jasper F.
Abstract: Mineral dust is an important player in global air quality and climate, but little is known about its variability and trends under the simultaneous influence of climate and land cover changes, particularly in East Asia where intense land cover change has occurred in recent decades. Here we determined the interannual variability and trends in dust emission from the main East Asian dust sources and examined to what extent these variations and trends were driven by climatic or land cover changes. We first optimized the dust emission module in the GEOS-Chem chemical transport model with better representation of dust physics and dependence on vegetation and wind variability. We then conducted simulations to quantify the impacts of climate and land cover variability and trends on springtime dust emission over 1982–2010 from the Teklimakan Desert, Gobi Desert and the whole East Asian desert domain. We found that dust emission from Gobi decreased substantially from the 1980s to 1990s, and then slightly increased toward the 2000s, leading to an overall reduction by 35% over the whole period. These changes were predominantly driven by meteorological changes and the effects of land cover change were negligible. Dust emission from Teklimakan increased from the 1980s to 1990s, but decreased afterward, leading to an overall reduction by 20%, albeit with large interannual variability. The overall trend was attributable to a consistent reduction in dust emission due to enhanced vegetation density in the periphery of the desert, accompanied by larger but more varying changes due to meteorological factors. Time series comparison and regression analysis indicated that in both deserts (especially Gobi), surface wind speed, followed by total precipitation, was the most important meteorological factor controlling dust variability and trends, with the weakening of wind playing the largest role in the overall decline in dust emission over the whole period. Overall, the interannual variability and trends of East Asian dust emission are largely shaped by climatic factors, with the land cover playing secondary but locally important roles, especially in the semiarid and non-desert regions undergoing rapid land cover change and desertification. Highlights: Dust emission in Gobi significantly decreased due to meteorological changes. There were no significant trends for dust emission in Teklimakan. Dust emission changes were controlled predominantly by climate variability. Land cover change was regionally important for dust changes in Teklimakan. Wind and precipitation were dominant drivers for dust emission variability.